Kaiwa Learning Effectiveness using Interview Method in Improving Japanese Speaking Comprehension - Alo Karyati; Paramita Winny Hapsari (Universitas Negeri Semarang, 2019)
This study aims is to: (1) Determine LPK Matsushita Gobel Foundation Jakarta participants ability to speak Japanese before using interview method. (2) Determine Pakuan University participant’s ability to speak in Japanese before using interview method. (3) Knowing the differences of LPK Matsushita Gobel Foundation Jakarta participant’s ability to speak Japanese before and after using the interview method. (4) Determine whether the method can improve the LPK Matsushita Gobel Foundation Jakarta participant’s ability to speak Japanese or not. (5) Gain feedback from LPK Matsushita Gobel Foundation Jakarta participants towards this method. This research is a class action, using a quasi-experiment which focuses on one sample class. The research instrument consists pretest and post-test, questionnaires, and interviews. The result of those interviews are reported in front of the class into a series of stories. By this method of interview, not only the participants are able to have conversations with many people, but the participants were able to reiterated the interview results to the class and done in a way such as giving a speech.